THE EFFECT OF AGE ON HAND GRIP STRENGTH IN THE ELDERLY IN KEDANYANG VILLAGE, KEBOMAS DISTRICT, GRESIK REGENCY - Aryan Rafly Firdausy; Rianti, Emillia Devi Dwi; Willianti, Enny (Calvaria Medical Journal, 2025)
Background: According to UNICEF (United Nations International Children Fund), Indonesia is a country with an increasing elderly population structure, and survey results show that the number of elderly people in Indonesia from 1990 to 2025 has increased. Factors that affect the quality of life of the elderly are physical health, psychological health, environment, and social relationships. The health of the elderly has a status with declining health conditions that are affected by age. Objectives: To find out the influence age on hand grip strength in the elderly in Keldanyang Village, Kebomas District, Gresik Regency. Methods: The sampling technique uses the total sampling technique. The independent variable in this study is the strength of the hand grip and the dependent variable is balance. The control variables in this study included age, gender, BMI (Body Mass Index), and the place where the research data was taken. This study is a type of observational analytical research and uses a research design with a Cross-Sectional approach. Results The results of the correlation test also showed that there was a significant relationship between age and hand grip strength, as evidenced by an r-value of -0.272 and a significance of 0.049 ± 0.05. Conclusions: This means that there is a significant relationship between the age of the respondents and the strength of the hands of the elderly in Kedanyang Village, Kebomas District, Gresik Regency.2. In the results of the respondents' descriptions based on Table V.7, it can be seen that the average grip strength of the hands of men is 33,863 kg, while the average of women is 18,939 kg. However, at an average age of 57.21 years, both men and women fall into the normal category for hand grip strength.